2013
DOI: 10.1127/0372-8854/2012/0080
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variability of river flows in the degraded semi-arid tropical mountains of northern Ethiopia

Abstract: Water availability has for long been a critical issue in many developing countries. Despite its enormous potential of water resources, Ethiopia is suffering from a lack of water availability and threatened by the consequences of climate change. Well considered planning to develop these resources is crucial. However, very few observational runoff data exist for this type of environments. Especially runoff data for catchments at the intermediate scale (100 -10,000 km²) are lacking. This study assesses the runoff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 24 publications
(38 reference statements)
6
34
0
Order By: Relevance
“…This trend was later echoed by other studies observing that soil moisture storage had to be filled before surface runoff was generated in Ethiopian highland watersheds (Bewket and Sterk, ). In semi‐arid areas such as Tigray, although infiltration excess by heavy storms is still important during the first phase of rainy period, saturation excess runoff dominates the second part of the rainy season (Descheemaeker et al ., ; Walraevens et al ., ; Zenebe et al ., ). Further studies have shown that soil saturation in (semi) humid experimental watersheds is the dominant mechanism for overland flow (Liu et al ., ; Collick et al ., ; Steenhuis et al ., ; Bayabil et al ., ; Tesemma et al ., ; Engda et al ., ) and for erosion (Tilahun et al ., ,).…”
Section: Introductionmentioning
confidence: 97%
“…This trend was later echoed by other studies observing that soil moisture storage had to be filled before surface runoff was generated in Ethiopian highland watersheds (Bewket and Sterk, ). In semi‐arid areas such as Tigray, although infiltration excess by heavy storms is still important during the first phase of rainy period, saturation excess runoff dominates the second part of the rainy season (Descheemaeker et al ., ; Walraevens et al ., ; Zenebe et al ., ). Further studies have shown that soil saturation in (semi) humid experimental watersheds is the dominant mechanism for overland flow (Liu et al ., ; Collick et al ., ; Steenhuis et al ., ; Bayabil et al ., ; Tesemma et al ., ; Engda et al ., ) and for erosion (Tilahun et al ., ,).…”
Section: Introductionmentioning
confidence: 97%
“…In situ soil conservation and water harvesting (Nyssen et al ., ; Gebreegziabher et al ., ; Nyssen et al ., ; Adimassu et al ., ; Mekonnen et al ., ) as well as the construction of small reservoirs (Haregeweyn et al ., ; Haregeweyn et al ., ) have both led to strongly decreased sediment yield and runoff coefficients at catchment scale, and to increased levels of the water tables (Nyssen et al ., ; Walraevens et al ., ) and have improved livelihood, as reported also elsewhere in Africa (Wildemeersch et al ., ). However, significant differences in runoff coefficients could not be demonstrated between subcatchments of the 5000 km 2 Geba basin, most probably due to the overall implementation of SWC activities (Zenebe et al ., ). Particularly in cases of large conversions to forest, such as the area upstream of Alamata, effects are very clear, especially in terms of decreased downstream flooding and changes of river channel morphology (i.e.…”
Section: Conservation Efforts and Effect On Water Availabilitymentioning
confidence: 97%
“…Yet, the exact mechanisms and sediment sources are being scrutinized more recently in the Amhara sub-humid region (Bayabil et al, 2010;Setegn et al, 2010;Tebebu et al, 2010Tebebu et al, , 2015. Comparisons with the drier Tigray region (Nyssen et al, 2006;Vanmaercke et al, 2010;Walraevens et al, 2009;Zenebe et al, 2013) are helping to better understand and evaluate the performance of soil and water conservation measures. The quick generation and increased runoff and sediment in Shanko Bahir relative to the nearby sub-watershed were observable during field work and complicated previous modeling efforts .…”
Section: Discussionmentioning
confidence: 99%
“…In the semi-arid highlands of Ethiopia, studies have also shown the presence of saturation-excess as a mechanism, however, only during certain parts of the rainy season. In Tigray, infiltration-excess overland flow caused by heavy or high intensity storms has been shown to be common early in the rainy season (Descheemaeker et al, 2009;Walraevens et al, 2009;Zenebe et al, 2013). Thus, although these regimes occur with varying intensity in different watersheds, few attempts had been made to integrate both mechanisms in a satisfactory way.…”
Section: Contributing Runoff Mechanisms and Roads In The Subhumid Ethmentioning
confidence: 99%